PERLINDUNGAN HUKUM KONSUMEN PENYANDANG DISABILITAS DAN LANJUT USIA DALAM INDUSTRI ASURANSI DI INDONESIA - Praningsih, Cerry; Rahardiansyah, Trubus (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: this study aims to analyze legal protection for persons with disabilities and the elderly in Indonesia’s insurance industry through a normative approach that combines literature review and limited interviews with three anonymous sources representing regulators, insurance practitioners, and disability organizations. The analysis employs Satjipto Rahardjo’s sociology of law and progressive law theories, as well as Lawrence M. Friedman’s legal system theory. The findings indicate that despite existing regulations—such as Law Number 8 of 2016 on Persons with Disabilities, Law Number 13 of 1998 on the Welfare of the Elderly, and the Financial Services Authority (OJK) regulations—providing a strong legal foundation, discrimination, limited access, and insufficient adaptation of insurance products for vulnerable groups are still present in practice. These obstacles are linked to institutional, legal substance, and legal culture aspects. The study recommends strengthening inter-agency coordination, optimizing the role of the National Commission on Disabilities (KND), and implementing affirmative policies in the insurance industry.Keywords: Consumer Protection, Disabilities, Elderly, Insurance Industry, Inclusion.